Research on the Calculation Model and Algorithm Convergence of Cylindrical Fin-tube Heat Exchanger - Peng Wenhao; Gu Bo; Zeng Weijie (Zhileng xuebao)
Cylindrical fin-tube is a new type of heat exchanger, and its mathematical calculation model has not been researched sufficiently. This study establishesa row-parameter model to realize the numerical calculation of cylindrical fin-tube heat exchangers, i.e., the exchanger is divided into a network of single-row heat exchange tubes andeach row is regarded as a heat exchanging unit. The numerical method presents an iterative solution of heat transfer equations using dichotomy method. The convergence problem in the iterative solution of single-row tubes was discussed in detail. Two iterative criteria were mentioned to guarantee the correct lower limit of the iteration variable (inlet temperature of water of each row). The algorithm was verified, and the results showed that the lower limit of the iteration variable is a linearly increasing function of the inlet water temperature of the heat exchanger. Moreover, for pipelines close to the water outlet of the heat exchanger, the lower limit temperature is higher than the total inlet temperature, which means that the algorithm has practical physical meaning, and could avoid the iteration into the unreasonable interval.